Effect of ramadan fasting on glycemic control and other essential variables in diabetic patients - Bener, Abdülbari; Al-Hamaq, Abdullah Omar; Öztürk, Mustafa; Çatan, Funda; Haris, Parvez; Rajput, Kaleem; Ömer, Abdülkadir (Medknow, 2018)
Fasting during the holy month of Ramadan is a religious obligation for all Muslims who represent 1.8 billion of the world population (24%). This study explores the effect of Ramadan fasting on the blood glucose, glycated hemoglobin (HbA1c), lipid profile, sleeping quality, and essential lifestyle parameters and also explores the safety of fasting for a whole month among diabetic patients.The aim of the present study was to assess the impact of Ramadan fasting on the blood glucose, HbA1c, lipid profile, sleeping quality, and lifestyle parameters among patients with type 2 diabetes mellitus (T2DM) in Turkey.A total of 1780 diabetic patients were approached, and 1246 (70%) participated in this cross-sectional study carried out during the period from May 27, 2017, to June 24, 2017. Data analysis comprised sociodemographic features, lifestyle habits, blood pressure measurements, serum lipid profiles, serum calcium, Vitamin D 25-hydroxy, uric acid, and HbA1c at before 4 weeks and after 12 weeks from Ramadan.Out of 1246 patients, 593 (47.6%) were male and 653 (52.4%) were female. The mean ± standard deviation age of the patients was 50.39 ± 15.3 years. Males were significantly older than females (51.53 ± 12.56 vs. 49.26 ± 14.4; P = 0.003, respectively). Significant differences were found in Vitamin D, blood glucose, HbA1c level, creatinine, bilirubin, albumin, total cholesterol, triglycerides, high-density lipoprotein-cholesterol (female), low-density lipoprotein-cholesterol (male), uric acid, and systolic and diastolic blood pressure after and before the holy month of Ramadan (P < 0.05 for each). HbA1c (P < 0.001), physical activity (P < 0.001), hours of sleeping (P < 0.001), systolic blood pressure (BP) (mmHg) (P = 0.007), BMI (P = 0.016), diastolic BP (mmHg) (P = 0.018), family history (P = 0.021), and smoking (P = 0.045) were identified as significantly associated with Ramadan fasting as contributing factors.In one of the largest studies of its kind, we show that Ramadan fasting has positive effects on T2DM patients as it reduces their blood pressure, blood glucose, HbA1C, and BMI. Furthermore, there are improvements in the duration of sleep and physical activity, the role of Ramadan fasting in diabetes therapy has been confirmed.
Keywords: Adult; Blood Glucose; Male; Turkey; Blood Pressure; Islam; Body Mass Index; Surveys and Questionnaires; Diabetes Mellitus; Humans; Life Style; Triglycerides; Glycated Hemoglobin; Cholesterol, HDL; Fasting; Middle Aged; Lipids; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Original Article; Female; Ramadan Fasting; Sleeping Quality; 3. Good health